Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1039/c8dt03343a
|View full text |Cite
|
Sign up to set email alerts
|

Donor-stabilised molecular Mg/Al-bimetallic hydrides

Abstract: Low-molecular organometallic hydride complexes of the type [(do)xMg{(μ2-H)(AlMe3)}2] form in ethereal solvents and display inherent reactivity of existing magnesium hydrido bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Much less is known of Ae metal complexes with the smallest aluminate anion AlH 4 – , which are expected to show lower solubilities. Fichtner et al reported the synthesis of Mg­(AlH 4 ) 2 and Ca­(AlH 4 ) 2 from the corresponding AeCl 2 and NaAlH 4 in ethereal solvents. , For Sr­(AlH 4 ) 2 , only a ball-milling route has been documented . We prepared these aluminates using the salt metathesis route mixing AeCl 2 (Ae = Mg, Ca, or Sr) and NaAlH 4 in THF in a 1/2 ratio (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Much less is known of Ae metal complexes with the smallest aluminate anion AlH 4 – , which are expected to show lower solubilities. Fichtner et al reported the synthesis of Mg­(AlH 4 ) 2 and Ca­(AlH 4 ) 2 from the corresponding AeCl 2 and NaAlH 4 in ethereal solvents. , For Sr­(AlH 4 ) 2 , only a ball-milling route has been documented . We prepared these aluminates using the salt metathesis route mixing AeCl 2 (Ae = Mg, Ca, or Sr) and NaAlH 4 in THF in a 1/2 ratio (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure of Mg­(AlH 4 ) 2 ·(THF) 4 is known and described as a complex in which both aluminate anions are bound to Mg 2+ in a H 3 Al-(μ-H)-Mg fashion (Figure a and Table ). The crystal structure of Ca­(AlH 4 ) 2 ·(THF) 4 is reported to be isostructural but of very poor quality, and hydride positions are uncertain . A high-quality structure, including refined hydride positions, is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methyl in [Cp*Be(μ‐Me)YbCp* 2 ] is a linear bridge [99] . [Cp*Mg(HAlMe 3 )(thf) 2 ] is liable to Schlenk equilibrium [100] . The Ph 2 P‐functionalized heavier metallocenes form PtMe 2 adducts [57e] .…”
Section: Cp’ (Cpr/indr/flur) Complexesmentioning
confidence: 99%
“…[99] [Cp*Mg(HAlMe 3 )(thf) 2 ] is liable to Schlenk equilibrium. [100] The Ph 2 P-functionalized heavier metallocenes form PtMe 2 adducts. [57e] Cp* 2 Ca forms 1 : 1 adducts with Cp* 2 HfCl 2 and [(mesitylene)Cr(CO) 3 ].…”
Section: (B) Heterobimetallic Complexesmentioning
confidence: 99%